RT-XAMF and TR-XRD Studies of Solid-State Synthesis and Thermal Stability of NaNiO2 as Cathode Material for Sodium-Ion Batteries - Kim, Dong Hyun; Kim, Ji Young; Park, Jae ho; Kim, Sang Ok; Kim, Hyung seok; Kim, Kwang-Bum; Chung, Kyung Yoon (Pergamon Press Ltd., 2022)
Room-temperature sodium storage technology has been attracting considerable attention, and its potential as a alternative technology to lithium-ion batteries for electrical energy storage has been studied owing to the abundance of sodium resources and its inexpensiveness. In situ X-ray diffraction (XRD) techniques, such as realtime X-ray analytical micro-furnace (RT-XAMF) and time-resolved X-ray diffraction (TR-XRD), are utilized to identify the synthesis process and thermal stability of the NaNiO2 cathode material for Na-ion batteries. Using the RT-XAMF technique, the solid-state reaction of Na2O2 and NiO was investigated in real-time to verify the phase transition from rhombohedral NaNiO2 at temperatures above 243 degrees C to monoclinic NaNiO2 at temperatures below 243 degrees C during heat treatment. In addition, the structural instability of the monoclinic NaNiO2 phase changes to the Na-deficient Na0.91NiO2 phase. The TR-XRD technique was used to investigate the thermal stability of the desodiated Na1_xNiO2 (x = 0.09, 0.5) cathodes in the presence of an electrolyte. It was confirmed that the structural changes of desodiated Na1_xNiO2 were relatively simple compared to those of the Ni-based cathode material in Li-ion batteries. First, the layered structure of Na1_xNiO2 at room temperature turns into an MO-type rock salt phase (NiO) and subsequently into a metallic phase (Ni) without the appearance of spineltype (Li1_ xM2O4 and M3O4) intermediates, which are typically observed in lithium nickel-based oxides. In addition, it was concluded that desodiated Na1_ xNiO2 materials have higher thermal stability than delithiated Li1_xNiO2 (x = 0.5, below -200 degrees C) based on its high decomposition temperature (-300 degrees C for Na0.91NiO2 and -280 degrees C for Na0.5NiO2). From these results, we believe that our in-situ XRD findings on the real-time solid-state synthesis process and thermal stability can be used as a fundamental guide for the development of Ni-based NaMO2 (M = Ni, Co, Mn, etc.) oxides for next-generation advanced Na-ion batteries.